Teachers' job satisfaction as mediator of the relationship between teachers' motivation and teachers' work performance: survey from secondary schools in Sarawak - Evonne Lai; Crispina Gregory K Han (ASIAN SCHOLARS NETWORK, 2019)
This paper is a quantitative research and procedures used to access and evaluate the statistical significance of relevant path coefficients were Smart-PLS measurement and structural model evaluation. The findings showed that the teaching task, additional task and administrative task have increased extrinsic and intrinsic satisfaction. Thus, this will improve teachers' performance more effectively because they have appropriate tasks in their working environment.